2014
DOI: 10.1515/med-2015-0016
|View full text |Cite
|
Sign up to set email alerts
|

Rare types of breast carcinoma

Abstract: AbstractBreast cancer (BC) is a heterogeneous disease that encompasses several distinct entities with remarkably different characteristics. Histological type is one of important BC characteristics. Histological type is associated with differences in epidemiology, diagnostic issues, clinical course, prognosis. When we talk about BC, ductal and lobular carcinoma is usually what we have in mind. However, the other types that comprise less than 10% of BC are also very important. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
(3 reference statements)
0
5
0
Order By: Relevance
“…The relative rarity of these subtypes is also reported in the South-Eastern [16], North-Eastern and South-Western parts of Nigeria [17,18]. Other parts of West Africa and the rest of the world also reported same pattern [19,20].…”
Section: Introductionmentioning
confidence: 73%
“…The relative rarity of these subtypes is also reported in the South-Eastern [16], North-Eastern and South-Western parts of Nigeria [17,18]. Other parts of West Africa and the rest of the world also reported same pattern [19,20].…”
Section: Introductionmentioning
confidence: 73%
“…Being the second most common epithelial type invasive lobular carcinoma (ILC) comprises of 5%-15% of the epithelial tumors [3] . Shakoor et al found that ILC was significantly more likely to spread to distant sites.…”
Section: Discussionmentioning
confidence: 99%
“…Most of breast carcinomas previously termed as "ductal" carcinomas are now categorized as "Invasive ductal carcinoma-no special type," (IDC-NOS) accounting to about 75% to 80%. Following it, the second most common type of breast carcinoma is the Invasive lobular carcinoma, representing about 5% to 15% [3] .…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that metastasis is responsible for almost 90% of cancer-related deaths [ 5 , 6 , 7 ], a hallmark ability of tumor cells to disseminate to distant organs throughout the body [ 8 , 9 ]. Several other studies have classified more rare subtypes of breast cancer with different behaviors and prognoses which help better define the characteristics and course of the disease [ 3 , 10 , 11 ]. It is worth mentioning that whether the BC is invasive or non-invasive will determine the patient’s treatment strategies and how they may respond to the treatments.…”
Section: Breast Cancer Pathogenesis and Subtypes (Histological And Mo...mentioning
confidence: 99%